Religious Leader’s Support toward Individual at Risk ofHIV/AIDS to Attend Voluntary Counselling and Testing Service - Manurung, Imelda Februati Ester; Wahyuni, Chatarina Umbul; Probandari, Ari (Kesmas, 2020)
Religious leader is a figure who is believed to have the gift of healing. A person with illness will follow any advice the religious leader gives for his/her recovery.Based on the phenomenon, religious leader is a potential local figure to give support for individuals at risk of human immunodeficiency virus (HIV) andacquired immune deficiency syndrome (AIDS). This study aimed to determine factors related to religious leader’s support toward individuals at risk of HIV andAIDS to attend voluntary counselling and testing (VCT) service. This study was an observational analytical with cross-sectional design. The population of thisstudy was religious leader in Kupang City. The sample size was 70 people selected through random sampling technique. The data were collected using questionnaire and analyzed using chi-square and multiple logistic regression test. Factors significantly related to the religious leaders supports’ for individuals atrisk of HIV and AIDS to get VCT were knowledge (OR = 9.01; 95% CI = 1.73 - 47.07), servant leadership (OR = 11.67; 95% CI = 2.44 - 55.84, trust (OR =11.55; 95% CI = 2.35 - 56.70) and perception (OR = 6.12; 95% CI = 1.26 - 29.71). Social capital had no significant effect on the religious leader support’s (OR= 1.06; 95% CI = 0.22 - 5.12). It is necessary to improve religious leader’s knowledge of HIV and AIDS.